ISOLASI DAN IDENTIFIKASI BAKTERI ASAM LAKTAT (BAL) PADA FERMENTASI BUAH DURIAN (Jruek Drien) - Yulia Sari Ismail; Cut Aja Laila; Iqbar Iqbar; Zulia Ananda (Universitas Syiah Kuala, 2025)
The process of making durian fermentation in Indonesia has many variations, including the addition of salt and turmeric with a shelf life of 3-5 days. These different processing methods can affect the growth, type, amount and production of lactic acid from LAB bacteria. This study aims to determine the type of LAB in durian fermentation added with salt, turmeric and a combination of both. Isolation was done aseptically using MRS media and incubated at 370C for 48 hours. Furthermore, identification was carried out, namely morphological observations and biochemical tests. Based on the test results, one type of LAB isolate was obtained, namely Lactobacillus casei.